Comment on "Cosmogenic neon in grains separated from individual chondrules: Evidence of precompaction exposure in chondrules" by J. P. Das, J. N. Goswami, O. V. Pravdivtseva, A. P. Meshik, and C. M. Hohenberg. (24th July 2013) - Ott, U.; Wieler, R.; Huber, L.
Abstract Das et al. (2012) claim that in several cases nominal cosmic ray exposure ages derived from concentrations of cosmogenic Ne in individual olivine grains separated from chondrules substantially exceed exposure ages of matrix samples. Some grains were also reported to show larger apparent exposure ages than other grains from the same chondrule. The authors conclude that the excesses were caused by an exposure of chondrules to high fluences of solar energetic particles and suggest that their data provide direct evidence for a highly active phase of the early Sun, similar to what is observed in X‐ray emissions of recent naked T‐Tauri stars. Here, we show that the production rates of cosmogenic Ne used by Das et al. (2012) to derive nominal cosmic ray exposure ages of their olivine grains are often much too low, as the reported major element concentrations in many cases sum up to considerably less than 100% even if converted to oxides. In contrast, adopted element concentrations for matrix samples are basically self‐consistent. A precompaction exposure of chondrules to a very high flux of solar energetic particles is thus not supported by the data presented by Das et al. (2012). Das et al. (2012) claim that in several cases nominal cosmic ray exposure ages derived from concentrations of cosmogenic Ne in individual olivine grains separated from chondrules substantially exceed exposure ages of matrix samples. Some grains were also reported to show larger apparent exposure ages than other grains from the same chondrule. The authors conclude that the excesses were caused by an exposure of chondrules to high fluences of solar energetic particles and suggest that their data provide direct evidence for a highly active phase of the early Sun, similar to what is observed in X‐ray emissions of recent naked T‐Tauri stars. Here, we show that the production rates of cosmogenic Ne used by Das et al. (2012) to derive nominal cosmic ray exposure ages of their olivine grains are often much too low, as the reported major element concentrations in many cases sum up to considerably less than 100% even if converted to oxides. In contrast, adopted element concentrations for matrix samples are basically self‐consistent. A precompaction exposure of chondrules to a very high flux of solar energetic particles is thus not supported by the data presented by Das et al. (2012).